2021
DOI: 10.3390/jzbg2020012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enclosure and Environmental Enrichment on the Behaviour of Ring-Tailed Lemurs (Lemur catta)

Abstract: Environmental enrichment is widely used to improve the quality of life of animals under human care. To successfully implement enrichment programs, it is important to evaluate their effect in different enclosure types since housing conditions may change depending on external factors, such as husbandry, management, or seasonal variation. This study investigates how ring-tailed lemur (Lemur catta) behaviour changes with the availability of enrichment items and the type of enclosure the animals are housed in. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 48 publications
4
12
4
Order By: Relevance
“…The general aim of the study is to promote the expression of species-specific behavioral patterns and reduce ABRs and stress-related behaviors. In particular, thanks to the social structure and stability of the selected group [ 46 ] and the predictable husbandry routine [ 7 ], we expect to find low levels of agonistic, explorative, scent-marking, foraging and locomotor behaviors, and a higher level of resting and stress-related patterns (e.g., yawning, self-scratching and self-grooming [ 40 , 41 ] compared to studies performed in the wild, as reported also by previous research on captive lemurs [ 16 , 30 , 32 , 36 ]. We also expect to detect the occurrence of ARBs, as found by other scholars, and a higher level of affiliative behaviors with respect to other captive studies conducted on breeding groups [ 16 , 36 ].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The general aim of the study is to promote the expression of species-specific behavioral patterns and reduce ABRs and stress-related behaviors. In particular, thanks to the social structure and stability of the selected group [ 46 ] and the predictable husbandry routine [ 7 ], we expect to find low levels of agonistic, explorative, scent-marking, foraging and locomotor behaviors, and a higher level of resting and stress-related patterns (e.g., yawning, self-scratching and self-grooming [ 40 , 41 ] compared to studies performed in the wild, as reported also by previous research on captive lemurs [ 16 , 30 , 32 , 36 ]. We also expect to detect the occurrence of ARBs, as found by other scholars, and a higher level of affiliative behaviors with respect to other captive studies conducted on breeding groups [ 16 , 36 ].…”
Section: Introductionmentioning
confidence: 80%
“…In particular, thanks to the social structure and stability of the selected group [ 46 ] and the predictable husbandry routine [ 7 ], we expect to find low levels of agonistic, explorative, scent-marking, foraging and locomotor behaviors, and a higher level of resting and stress-related patterns (e.g., yawning, self-scratching and self-grooming [ 40 , 41 ] compared to studies performed in the wild, as reported also by previous research on captive lemurs [ 16 , 30 , 32 , 36 ]. We also expect to detect the occurrence of ARBs, as found by other scholars, and a higher level of affiliative behaviors with respect to other captive studies conducted on breeding groups [ 16 , 36 ]. We hypothesize that the selected enrichment items will increase the expression of exploratory, foraging, locomotion and scent-marking patterns, reduce resting and stress-related behaviors, and have a neutral effect on affiliative and agonistic ones.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Providing appropriate enrichment items can increase the activity level and natural behaviour of the animals by offering them opportunities to engage in species-appropriate behaviours [19,35,38]. It has been suggested that observing active and engaged animals could promote positive visitor perceptions towards them [28].…”
Section: Discussionmentioning
confidence: 99%
“…In these items, a third of the lemurs' daily diet was included to avoid overfeeding. All devices used in this study had been previously offered to the lemurs during another research conducted by our group [35], and were therefore not novel to the animals.…”
Section: Enrichment Itemsmentioning
confidence: 99%